Concretos refratários fosfatados para refino de petróleo: caracterização, propriedades e adequação ao uso - Gomes, Daniel Telhado (2018)
The increasing demand for petroleum experienced in the last decades has pushed the barrel price to a level never seen before, stimulating a race for rising production volumes and taking us to even deeper waters. On a similar move, the refining industry has adapted itself and optimized its processes, resulting in higher unit operational availability. During this period, one of the initiatives explored to reduce maintenance downtime was the increment of phosphate-bonded refractories installation, replacing the cement based castables. In addition of satisfactory thermo-mechanical properties up to 1,500 °C, these products allow high heating rates after curing without explosion risk and chemical adhesion on pre-fired refractory linings, speeding up equipment’s repair. Despite the advantages, the shortage production of these materials in Brazil required its importation, turning costs 5–15 times higher than those for conventional castables. Prospecting potential new suppliers, this work characterized imported and previously qualified phosphate-bonded products, comparing them with those newly developed by national manufacturers, aiming to evaluate the performance and suitability for using these formulations. The results showed that in many aspects the national materials overcame the previously qualified references, being viable options for using in oil refineries. On the other hand, it was also observed the need of improvement and adjustments, motivating the development of a second generation of phosphate-bonded castable refractories in Brazil. Based on the obtained results, requirements were also proposed for materials specification.